1995
DOI: 10.1063/1.113337
|View full text |Cite
|
Sign up to set email alerts
|

Fast thermoelectric response of normal state YBa2Cu3O7−δ films

Abstract: Articles you may be interested inThe role of a-axis grains in the transition to the normal state of YBa2Cu3O7−δ films and of 2G-coated conductors when induced by high electrical current densities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 9 publications
3
27
0
Order By: Relevance
“…The laser induced thermoelectric voltage (LITV) effect was firstly found in normal state YBa 2 Cu 3 O 7-d thin films [1][2][3][4], which initiated a large number of investigations on this effect as it has great potential application in photoelectric detectors, thermoelectric detectors and for conversion of waste heat to electricity. Untill now, this effect in Bi 2 Sr 2 CaCu 2 O 8 [5], La 1 À x Ca x MnO 3 [6][7][8], La 1 À x Pb x MnO 3 [9], La 2 À x Sr x CuO 4 [10], Ca x CoO 2 [11][12][13] and Bi 2 Sr 2 Co 2 O y [14] thin films has been investigated when films are tilted.…”
Section: Introductionmentioning
confidence: 99%
“…The laser induced thermoelectric voltage (LITV) effect was firstly found in normal state YBa 2 Cu 3 O 7-d thin films [1][2][3][4], which initiated a large number of investigations on this effect as it has great potential application in photoelectric detectors, thermoelectric detectors and for conversion of waste heat to electricity. Untill now, this effect in Bi 2 Sr 2 CaCu 2 O 8 [5], La 1 À x Ca x MnO 3 [6][7][8], La 1 À x Pb x MnO 3 [9], La 2 À x Sr x CuO 4 [10], Ca x CoO 2 [11][12][13] and Bi 2 Sr 2 Co 2 O y [14] thin films has been investigated when films are tilted.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5]12,13 These voltage signals showed very fast evolution and decay time of several 10 ns, which suggested that the incline-oriented films can be potential candidates for thermal-type optical detectors with high-speed. Also, the "V x 6 k DT z " feature allows us to independently modify the electric and thermal design of the films, which makes this phenomenon more attractive for device development.…”
mentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Pioneering studies on YBa 2 Cu 3 O 7-d thin films have revealed that this phenomenon emerges uniquely in anisotropic materials when they are fabricated in an inclined crystallographic orientation. [1][2][3][4][5] Figure 1(a) shows an example of the crystallographic orientation necessary to develop the ODTE effect. The material shown here is a layered cobaltite Ca x CoO 2 , which exhibits highly anisotropic properties between the ab plane and the c axis.…”
mentioning
confidence: 97%
“…The coherent growth of such films on appropriately oriented substrates has been established by the observation of a tilt angle dependent lateral thermoelectric effect in the normal state. 7 These films, available as fast optical radiation detectors ͑ForTech HTS, Regensburg, Germany͒, have a response extending from UV to FIR wavelengths.…”
mentioning
confidence: 99%